Association between homocysteine and Glycated Hemoglobin in pre-diabetic and diabetic patients of Karachi Pakistan - Jamali, Ghulam Murtaza; Iqbal, Sahar; Naeem, Syed Talha; Ahmed, Humaira; Khan, Fouzia Zeeshan (International Journal of Pathology, 2025)
Background: Diabetes Mellitus (DM) is a metabolic disorder related to high morbidity and mortality. This study aims to investigate the relationship between plasma homocysteine (Hcy) levels and Glycated Hemoglobin A1c (HbA1c) levels in individuals with pre-diabetes and diabetes mellitus. Methods: This study was conducted at the Department of Chemical Pathology, Dow University of Health Sciences (DUHS), Karachi, involving 148 participants (74 pre-diabetic, 74 diabetic). Plasma Hcy levels and HbA1c levels were measured using the Siemens Atellica Analyzer. Statistical analysis was performed using SPSS version 26. Mann-Whitney U test, Spearman’s correlation, and linear regression were used to analyze data, considering level of significance (p<0.005). Results: Diabetic participants had significantly higher Hcy levels (31.94 ± 8.88 µmol/L) compared to pre-diabetic individuals (26.55 ± 12.57 µmol/L) (p < 0.001). HbA1c levels were also significantly higher in diabetics (7.97 ± 0.98%) compared to pre-diabetics (6.05 ± 0.18%) (p < 0.001). Weak but significant positive correlation was observed between Hcy and HbA1c (r = 0.225, p = 0.006). Linear regression analysis showed that Hcy levels explained 4.9% of the variance in HbA1c levels (R = 0.222, p = 0.007). Conclusion: We observed a weak but statistically significant association between hcy and HbA1c levels. It highlights the need for further research to explore potential mechanisms and confounding factors.